FYR of Macedonia : Public Expenditure and Institutional Review - World Bank (Washington, DC, 2013)
The review was undertaken, and completed against a background of substantial political economic disruption: the Kosovo crisis of 1999 threatened to undermine the country's accomplishments in building macroeconomic, and fiscal stability; and, the security crisis of 2001, tested once again Macedonia's political, and economic integrity. Both instances were successfully surpassed, showing significant steps towards becoming a market oriented state within the European context, and, in its willingness to accept, and ratify the Peace Agreement of November 2001. But, expenditure pressures rose, leading to additional spending, while revenues declined owing to economic weakness, and decreased tax enforcement; clearly, fiscal stability stands on the balance. Not surprising, the quality of expenditures became an important issue, for although acceptable aggregate targets were being achieved, the budget's economic composition was not suited for promoting economic growth. Institutional aspects show that budget preparation, and processes provide no link between policy commitments, and available resources, aggravated by unfounded credibility on the budget, as an instrument for policy formation. Recommendations call for improved resource allocation within fiscal constraints, i.e., reducing public resources, and, laying the foundation for a budget process legal framework. In addition, reforms should be institutionalized through accountability, and capacity building.